International human resource management - Dowling, Peter J.; Festing, Marion; Engle, Allen D. (Cengage Learning Emea, 2017)
Now on its seventh edition, International Human Resource Management is established as a market leader that caters to students worldwide. This textbook has developed alongside the field - helping to shape what it is today - and remains a leading International Human Resources Management (IHRM) textbook worldwide. International Human Resource Management provides an academic overview of global IHRM, whilst still remaining close to curriculum developments. This textbook also contains nine in-depth case studies written by the authors and global experts, that provide a range of in-depth applications for all of the major functional areas of IHRM.